2017
DOI: 10.5455/njppp.2017.7.0203427062017
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sleep in hypothyroid patients with normal controls

Abstract: Background: Sleep -A complex amalgam of behavioral and electrophysiological process is maintained by organized interaction between neurons, neural circuits, and neurotransmitters. Hypothyroidism is the inadequate secretion of thyroid hormones by the thyroid gland. Hypothyroidism, the 2 nd common endocrine disorder, is often accompanied by complaints of daytime fatigue. This chronic fatigue should be managed as it may result in impaired attention with adverse consequences in the classroom, workplace, not to for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…In hypothyroid patients, T4 insufficiency is now considered to be the main cause of fatigue and sleepiness. Total sleep time is not significantly altered in hypothyroid patients but is mainly characterized by decreased non-rapid eye movement 1 (N1) and non-rapid eye movement 2 (N2) as well as non-rapid eye movement 3 (N3) and REM, suggesting poor sleep quality [42,43]. Another study suggested that hypothyroidism may lead to a reduction in the number of awakenings and slow-wave sleep (SWS) through a mechanism related to disturbances in thyroid hormone, TSH, and TRH secretion [44][45][46][47].…”
Section: Non-rapid Eye Movementmentioning
confidence: 99%
“…In hypothyroid patients, T4 insufficiency is now considered to be the main cause of fatigue and sleepiness. Total sleep time is not significantly altered in hypothyroid patients but is mainly characterized by decreased non-rapid eye movement 1 (N1) and non-rapid eye movement 2 (N2) as well as non-rapid eye movement 3 (N3) and REM, suggesting poor sleep quality [42,43]. Another study suggested that hypothyroidism may lead to a reduction in the number of awakenings and slow-wave sleep (SWS) through a mechanism related to disturbances in thyroid hormone, TSH, and TRH secretion [44][45][46][47].…”
Section: Non-rapid Eye Movementmentioning
confidence: 99%